SISTEM KEKERABATAN DALAM BAHASA BATAK KARO JAHE DI DESA BANGUN PURBA KECAMATAN BANGUN PURBA KABUPATEN DELI SERDANG - Nurmala Nurmala; Sudartomo Macaryus (Universitas Sarjanawiyata Tamansiswa, 2016)
The purpose of this study (1) describes the classification requirements of the relatives of three generations above and three generations under language ego village of Batak Karo Jahe Bangun Purba (2) describes the components of meaning in terms of kinship three generations above and three generations under ego in the village language of Batak Karo Jahe in Bangun Purba.This research is qualitative. This research data in the form of words used by the community kinship Karo dialect. Sources of data in this study are primary and secondary data. Sources of primary data from interviews with native speakers source Batak Karo Jahe village in Bangun Purba. Secondary data sources from a research report conducted by Mukhamdanah, et al